The Trafficking of the Water Channel Aquaporin-2 in Renal Principal Cells—a Potential Target for Pharmacological Intervention in Cardiovascular Diseases - Vukićević, Tanja; Schulz, Maike; Faust, Dörte; Klussmann, Enno (Frontiers in Pharmacology, 2016)
Arginine-vasopressin (AVP) stimulates the redistribution of water channels, aquaporin-2 (AQP2) from intracellular vesicles into the plasma membrane of renal collecting duct principal cells. By this AVP directs 10 % of the water reabsorption from the 170 L of primary urine that the human kidneys produce each day. This review discusses molecular mechanisms underlying the AVP-induced redistribution of AQP2; in particular, it provides an overview over the proteins participating in the control of its localization. Defects preventing the insertion of AQP2 into the plasma membrane cause diabetes insipidus. The disease can be acquired or inherited, and is characterized by polyuria and polydipsia. Vice versa, up-regulation of the system causing a predominant localization of AQP2 in the plasma membrane leads to excessive water retention and hyponatremia as in the syndrome of inappropriate antidiuretic hormone secretion (SIADH), late stage heart failure or liver cirrhosis. This article briefly summarizes the currently available pharmacotherapies for the treatment of such water balance disorders, and discusses the value of newly identified mechanisms controlling AQP2 for developing novel pharmacological strategies. Innovative concepts for the therapy of water balance disorders are required as there is a medical need due to the lack of causal treatments.